Taxonomy of the genus Erymus Bordoni (Coleoptera: Staphylinidae, Staphylininae, Xantholinini) in China with descriptions of two new species - Zhou, Yu-Lingzi; Zhou, Hong-Zhang (Zootaxa, 2014)
This paper studies the taxonomy of the genus Erymus Bordoni, 2002 (Coleoptera: Staphylinidae, Staphylininae, Xantholinini) from China. Two new species are described: Erymus wufengensis sp. n. from Hubei, and E. gilvus sp. n. from Hainan, Guangxi, and Guangdong provinces of China. The previously known four species of this genus are redescribed, and the identification key to all six Chinese species of the genus is provided. The type specimens of the new species are deposited in the Institute of Zoology, Chinese Academy of Sciences (IZ-CAS).